The Role of Community Health Nurses in Handling Dengue Fever Outbreaks in Residential Areas - Jasmin Ambas; Kamesyworo Kamesyworo; Herlina Lidiyawati (Oshada, 2024)
Controlling Dengue Hemorrhagic Fever (DHF) outbreaks is a complex public health challenge that requires collaboration from various stakeholders, including community health nurses. This study aims to assess the role of these nurses in managing DHF outbreaks in residential areas. Using a descriptive qualitative approach, the research involved in-depth interviews with community health nurses and direct field observations to gather comprehensive data. The findings revealed that community health nurses are crucial in preventing and controlling DHF outbreaks. Their responsibilities include educating the community about DHF prevention, identifying and managing mosquito breeding sites, and implementing environmental interventions. They also play a vital role in early detection of DHF cases and coordinate with government and health institutions for effective prevention and control measures. Furthermore, community health nurses provide counseling and training to raise awareness about DHF dangers and promote preventive actions. They are instrumental in encouraging community participation in environmental management to reduce mosquito habitats. This study emphasizes the need for ongoing support and capacity building for community health nurses to enhance their effectiveness. In conclusion, collaboration among health workers, communities, and stakeholders is essential to control dengue outbreaks and minimize the disease's impact.